2019
DOI: 10.3390/su11102830
|View full text |Cite
|
Sign up to set email alerts
|

A Simple GIS-Based Model for Urban Rainstorm Inundation Simulation

Abstract: With rapid urbanization, floods that occur are more frequently associated with non-riverine, urban flooding. Reliable and efficient simulation of rainstorm inundation in an urban environment is profound for risk analysis and sustainable development. Although sophisticated hydrodynamic models are now available to simulate the urban flooding processes with a high accuracy, the complexity and heavy computation requirement render these models difficult to apply. Moreover, a large number of input data describing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
(78 reference statements)
1
16
0
2
Order By: Relevance
“…Despite well-documented effects of manholes on urban flooding [19,20,37,41,42], there exists relatively limited research [43][44][45][46][47] that directly incorporate manhole overflow in simulations of urban flooding. Chen et al [48] used coupled surface and sewer flow modeling and found approximately 2 m surge flow from manholes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite well-documented effects of manholes on urban flooding [19,20,37,41,42], there exists relatively limited research [43][44][45][46][47] that directly incorporate manhole overflow in simulations of urban flooding. Chen et al [48] used coupled surface and sewer flow modeling and found approximately 2 m surge flow from manholes.…”
Section: Introductionmentioning
confidence: 99%
“…Epistemia,Vol. 6(2) 63 Luego se procedió con la secuencia de la investigación según se muestra en la figura 2, el cual inició con la aplicación del sistema de información geográfica, después se realizó el análisis de extremos de caudales máximos y finalmente el modelamiento hidráulico para generar los mapas de potenciales inundaciones, tal y como lo sugieren en sus investigaciones Meng et al (2019) y Zandiba-Siregar et al (2019.…”
Section: Materiales Y Métodosunclassified
“…At the same time, the theoretical research of producing and conflux of runoff gradually matures, and the model structure improves. A physical model has been developed and applied rapidly from lumped type to distributed type [9][10][11][12][13][14][15]. Although the distributed hydrological model based on complex physical mechanism can truly reflect the spatial variability of runoff and concentration process, the models have their applicable physical background, which limits the generality in all basins [16].…”
Section: Introductionmentioning
confidence: 99%